Lung ultrasound in the management of mechanical ventilation in pediatric critical care: a narrative review - Lopes, Nailu Lealina Garrido; Amaral, Vivian Henriques do; Minozzi, Marina Simões; Guazzelli Pitta Madureira, Paola; Zagne Braz, Luisa; da Hora Passos, Rogerio (Frontiers in Pediatrics, 2025)
Lung ultrasound (LUS) has become an increasingly valuable tool in the management of critically ill pediatric patients, offering dynamic, radiation-free bedside evaluation of pulmonary function. This narrative review synthesizes current evidence on the application of LUS in the context of ventilation in children and neonates. Key domains include its role in determining the indication for ventilation, guiding ventilatory adjustments, assessing positive end-expiratory pressure (PEEP) response, supporting lung recruitment maneuvers, and aiding in weaning and extubation decisions. The use of LUS in diagnosing ventilator-associated pneumonia (VAP) is also addressed, highlighting characteristic sonographic findings and their limitations. The I-VENT mnemonic is proposed as a practical framework for clinicians to integrate LUS into ventilatory management. While further research is needed to standardize protocols and validate scoring systems, current evidence supports the routine use of LUS in pediatric intensive care as a safe, accessible, and informative tool for optimizing respiratory support.